Two new species of the trapdoor spider genus Conothele Thorell, 1878 (Mygalomorphae: Halonoproctidae) from China - Yang, Zizhong; Xu, Xin (Zootaxa, 2018)
Here male specimens of the trapdoor spider family Halonoproctidae collected from Yunnan Province, China are diagnosed and described as new to science based on their genital morphology. Specimens are identified as two new species of Conothele Thorell, 1878: C. cangshan sp. nov. and C. deqin sp. nov.